Uruguay : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision and Payment Systems. (IMF Staff Country Reports; Country Report, 2006)
Improved liquidity and capital adequacy have increased the Uruguayan banking system's capacity to withstand shocks. However, macroeconomic and financial risks remain owing to the high level of government debt, guarantees to state banks, high dollarization, and a high share of nonresident deposits. The insurance sector also suffered from the crisis, but the pension system weathered it relatively well. The authorities implemented a stabilization program following the crisis. Capital markets in Uruguay are small and illiquid. The proposed amendments are improving the autonomy and accountability of banks.